2016
DOI: 10.2495/sdp-v11-n6-897-906
|View full text |Cite
|
Sign up to set email alerts
|

Vitrified hillforts as anthropogenic analogues for nuclear waste glasses – project planning and initiation

Abstract: Nuclear waste must be deposited in such a manner that it does not cause significant impact on the environment or human health. In some cases, the integrity of the repositories will need to sustain for tens to hundreds of thousands of years. In order to ensure such containment, nuclear waste is frequently converted into a very durable glass. It is fundamentally difficult, however, to assure the validity of such containment based on short-term tests alone. To date, some anthropogenic and natural volcanic glasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Scandinavian researchers proposed that vitrification was instead related to building processes. Having analysed data from the Viking village of Broborg, they concluded that it would have been a gradual and intentional process intended to strengthen the ramparts (Kresten & Ambrosiani, 1992: 1; Sjöblom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Scandinavian researchers proposed that vitrification was instead related to building processes. Having analysed data from the Viking village of Broborg, they concluded that it would have been a gradual and intentional process intended to strengthen the ramparts (Kresten & Ambrosiani, 1992: 1; Sjöblom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%